How CSR Disclosure Bridges Environmental Performance and Tax Avoidance - Ahmad Bukhori Muslim; Benny Oktaviano; Neng Asiah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study examines the relationship between Corporate Social Responsibility (CSR) disclosure, environmental performance, and tax avoidance among food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. The research aims to determine whether CSR disclosure acts as a bridge linking environmental responsibility and fiscal behavior, and whether environmental performance moderates this relationship. Using a quantitative approach, data were collected from annual and sustainability reports, yielding 76 firm-year observations analyzed through multiple linear regression with moderating effects. The findings reveal that CSR disclosure has a significant negative effect on tax avoidance, while environmental performance also negatively affects tax avoidance and strengthens the impact of CSR disclosure. These results support the ethical alignment channel, suggesting that companies with strong environmental and social commitments tend to demonstrate higher fiscal responsibility. The implications of this study highlight the importance of integrating CSR and environmental strategies into corporate governance to promote transparency, ethical taxation, and sustainable business practices in Indonesia’s manufacturing sector.